Introduction of the Anspach drill as a novel surgical driller for creating calvarial defects in animal models. Issue 5 (1st April 2019) - Guillaume, Olivier; Schmid, Tanja; Kluge, Katharina; Weber, Franz E.; Richards, Robert Geoff; Eberli, Ursula; Eglin, David; Zeiter, Stephan
ABSTRACT: Standardized and reproducible animal models are required for the assessment of bone healing mediated by biomaterials, cells, and drugs. Among the available bone‐fractured models, calvarial defect is a simple and adequate option when researchers investigate intra‐membranous bone formation and the influence of their regenerative solutions. However, the conventional surgical tools required to perform calvaria osteotomies (i.e., trephine bur mounted on a dental handpiece, DS) can affect the subjacent tissues of the skull, which are the dura mater and the brain. We hypothesized that the quality of the calvaria defect and the preservation of underlying tissues can be improved using a novel Anspach high‐speed drill with a Codman Neuro Disposable Perforator handheld (ACP). Using a rabbit cadaveric models, we performed calvarial defects with either conventional DS or the ACP system, and showed that both techniques allowed to create standardized defects with circular geometry. We demonstrated that the ACP had clear benefices in terms of DM preservation and absence of exothermic reaction upon drilling. Even though this comparative work was conducted on cadaver, it is of substantial importance as it introduces a novel technique, easily applicable to investigate calvaria bone healing, which brings clear advantages compared to the conventional dental station. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 9999:1–9, 2019.